Combine like terms
3f - 5g - f - 2g...lets do some rearranging to make it easier
3f - f - 5g - 2g =
2f - 7g <===
Answer:
1. y = - 4 x + 5
2. x = -8
Step-by-step explanation:
1. (-1,9) (1,1)
y = mx + b
m = (y-y') / (x-x') = (1-9) / (1-(-1)) = -8 / 2 = - 4
b = y - mx = 9 - (-4) x (-1) = 5
equation: y = - 4 x + 5
check: (1,1) y=1 = (-4) x 1 + 5 = 1
2. Vertical line through (-8,6) is a line perpendicular to x axis
x = -8
This situation can be represented by a step function.If Jalyn purchases 60 shirts the total cost will be $600.At these prices it is cheaper to buy 76 shirts than it is to buy 75 shirts.
500 + 30% equals 650. 30% of 500 equals 150.